Corporate Culture, Customer Orientation, and Innovativeness in Japanese Firms: A Quadrad Analysis - Deshpandé, Rohit; Farley, John U.; Webster, Frederick E. (Journal of Marketing, 1993)
“Quadrads” (double dyads) of interviews, each conducted with a pair of marketing executives at a Japanese vendor firm and a pair of purchasing executives at a Japanese customer firm, provided data on corporate culture, customer orientation, innovativeness, and market performance. Business performance (relative profitability, relative size, relative growth rate, and relative share of market) was correlated positively with the customer's evaluation of the supplier's customer orientation, but the supplier's own assessment of customer orientation did not correspond well to that of the customer. Japanese companies with corporate cultures stressing competitiveness (markets) and entrepreneurship (adhocracies) outperformed those dominated by internal cohesiveness (clans) or by rules (hierarchies). Successful market innovation also improved performance.